Hydrogel-based Drug Delivery System in Diabetes Management - Saharan, Renu; Kaur, Jaspreet; Dhankhar, Sanchit; Garg, Nitika; Chauhan, Samrat; Beniwal, Suresh; Sharma, Himanshu (Pharmaceutical Nanotechnology, 2024)
Background: It is estimated that there are over 200 million people living with diabetes mellitus (DM) all over the world. It is a metabolic condition caused by decreased insulin action or secretion. Diabetes Mellitus is also known as Type 2 Diabetes Mellitus. Type 1 diabetes mellitus and type 2 diabetes mellitus are the two most common types of DM. Treatment for type 1 diabetes often consists of insulin replacement therapy, while treatment for type 2 diabetes typically consists of oral hypoglycemics. Objectives: Conventional dosing schedules for the vast majority of these medications come with a number of drawbacks, the most common of which are frequent dosing, a short half-life, and low bioavailability. Thus, innovative and regulated oral hypoglycemic medication delivery methods have been developed to reduce the limitations of standard dose forms. Methods: The studies and reviews published under the title were looked up in several databases (including PubMed, Elsevier, and Google Scholar). Results: Hydrogels made from biopolymers are three-dimensional polymeric networks that can be physically or chemically crosslinked. These networks are based on natural polymers and have an inherent hydrophilic quality because of the functional groups they contain. They have a very high affinity for biological fluids in addition to a high water content, softness, flexibility, permeability, and biocompatibility. The fact that these features are similar to those of a wide variety of soft living tissues paves the way for several potentials in the field of biomedicine. In this sense, hydrogels offer excellent platforms for the transport of medications and the controlled release of those drugs. Additionally, biopolymer-based hydrogels can be put as coatings on medical implants in order to improve the biocompatibility of the implants and to prevent medical diseases. Conclusion: The current review focuses on the most recent advancements made in the field of using biopolymeric hydrogels that are physically and chemically crosslinked, in addition to hydrogel coatings, for the purpose of providing sustained drug release of oral hypoglycemics and avoiding problems that are associated with the traditional dosage forms of oral hypoglycemics.
Keywords: polymeric networks